2008
DOI: 10.5338/kjea.2008.27.4.406
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Greenhouse Gas Emissions from Livestock and Food Wastes Co-digestive Biogas Production System

Abstract: Biogas plant with anaerobic digestion is receiving high attention as a facility for both livestock waste treatment and electric power generation. Objective of this study was to perform life cycle assessment (LCA) of a biogas plant which incorporates swine and food waste (7:3) as source materials for biogas production. In addition, the biogas production process was compared with the prevalent composting method as a reference in the aspects of green house gas (GHG) reduction potential and environmental impact. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This expanding population will be a challenge for the livestock industry. However, there is limited data for GHG emissions from livestock agriculture over the past decade (Lee and Lee, 2003; Nam et al, 2008; Lim et al, 2011). Previous reports have emphasized quantifying CH 4 emissions during enteric fermentation for a national inventory, manure treatment facilities (Lim et al, 2011), livestock manure and waste co-digesting biogas (Nam et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This expanding population will be a challenge for the livestock industry. However, there is limited data for GHG emissions from livestock agriculture over the past decade (Lee and Lee, 2003; Nam et al, 2008; Lim et al, 2011). Previous reports have emphasized quantifying CH 4 emissions during enteric fermentation for a national inventory, manure treatment facilities (Lim et al, 2011), livestock manure and waste co-digesting biogas (Nam et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is limited data for GHG emissions from livestock agriculture over the past decade (Lee and Lee, 2003; Nam et al, 2008; Lim et al, 2011). Previous reports have emphasized quantifying CH 4 emissions during enteric fermentation for a national inventory, manure treatment facilities (Lim et al, 2011), livestock manure and waste co-digesting biogas (Nam et al, 2008). Recently, Won et al (2014) found that CH 4 and N 2 O emissions from sows, layer chickens and Korean cattle were very different, and an increased C/N ratio was associated with higher CH 4 emissions, which were lower than the proposed values from the Intergovernmental Panel on Climate Change (IPCC, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches on GHG emissions from livestock agriculture in Korea have been focused on the quantifying CH 4 emission during enteric fermentation for national inventory for CH 4 (Lee and Lee, 2003), the evaluation of GHG emissions during main processes in public livestock manure treatment facilities (Lim et al, 2011), and the evaluation of GHG emissions from livestock manure and food waste co-digesting biogas facility with the life cycle assessment (Nam et al, 2008). Currently local administrative districts are interested in the characteristics of their GHG emissions and GHG mitigation measures.…”
Section: Introductionmentioning
confidence: 99%